Efektivitas Subak Dalam Menanggulangi Alih Fungsi Lahan di Kawasan Warisan Budaya Dunia Jatiluwih - Andre Pradnya Yuda; Ida Ayu Putu Sri Widnyani; I Made Sumada (CV. AFDIFAL MAJU BERKAH, 2024)
Subak represents a distinctive agricultural culture in Bali, functioning as an indigenous community organization with significant socio-agrarian and cultural implications. The inclusion of Subak within the Jatiluwih World Cultural Heritage Area, recognized by UNESCO as a valuable intangible heritage, underscores its importance. However, the rapid expansion of tourism and service industries has raised concerns about land conversion, potentially jeopardizing agricultural productivity through the development of villas, homestays, and restaurants. The study employs qualitative research methods to systematically document and observe field information and phenomena. While Subak's role is deemed partially effective compared to non-designated counterparts, land conversion persists due to various factors including internal motivations, external environmental conditions, and regulatory frameworks governing land use. Enhancing integration is crucial, involving the design of additional regulations to fortify the eco-cultural tourism system and foster collaboration between agricultural and tourism sectors. There is a pressing need to increase support for Subak, encompassing both moral and material assistance.